MONITORING WATER LEVELS AS FLOOD DETECTORS BY UTILIZING TELEGRAM APPLICATIONS BASED ON IOT (INTERNET OF THINGS) - Muhammad Syahputra Novelan (Sean Institute, 2022)
Flood is a natural disaster that occurs when excessive flow of water will submerge the land. Floods also often occur because most of the garbage is thrown carelessly so that the drains or sewers are clogged especially with the continuous rain for days so that the overflow of water causes flooding and many casualties. To overcome this problem, there needs to be a solution so that there are no more casualties and losses, namely making a water level monitoring system by utilizing the telegram application as a notification medium. The system will be made by utilizing Arduino UNO as a controller and based on IoT (Internet Of Things) so that information can be sent accurately. This study aims to make the local community aware of overflowing water. The designed tool will automatically detect water from safe, alert and dangerous status. If the water level rises to a danger status, nature will issue an alarm sound and automatically send a message to the telegram application that the water level is in danger status. This system will later be implemented for the community in various flood-prone areas